2018
DOI: 10.3399/bjgp18x700205
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and referral delays in primary care for oral squamous cell cancer: a systematic review

Abstract: BackgroundThe incidence of oral cancer is increasing. Guidance for oral cancer from the National Institute for Health and Care Excellence (NICE) is unique in recommending cross-primary care referral from GPs to dentists.AimThis review investigates knowledge about delays in the diagnosis of symptomatic oral squamous cell carcinoma (OSCC) in primary care.Design and settingAn independent multi-investigator literature search strategy and an analysis of study methodologies using a modified data extraction tool base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 44 publications
(112 reference statements)
5
70
0
2
Order By: Relevance
“…However, these guidelines have been challenged by researchers due to the lack of accessible and affordable dental referral pathways for patients ( 80–82 ) in the UK, which could lead to further delays in diagnosis. Further, a recent systematic review of patient journeys in the diagnosis of oral cancer found no evidence to suggest that GPs performed less well than dentists in terms of referrals to specialists ( 81 ). Our findings along with previous research ( 75 , 81 ) suggest the need to also design and include a standard referral pathway globally for definitive care and management of oral cancer to reduce any further delays in initializing the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, these guidelines have been challenged by researchers due to the lack of accessible and affordable dental referral pathways for patients ( 80–82 ) in the UK, which could lead to further delays in diagnosis. Further, a recent systematic review of patient journeys in the diagnosis of oral cancer found no evidence to suggest that GPs performed less well than dentists in terms of referrals to specialists ( 81 ). Our findings along with previous research ( 75 , 81 ) suggest the need to also design and include a standard referral pathway globally for definitive care and management of oral cancer to reduce any further delays in initializing the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that the oral cavity is readily explorable, most oral tumors are diagnosed at an advanced stage reducing the survival rate of patients [19,20]. Currently, there are no effective biomarkers for the early diagnosis of oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Primary care physicians consistently are the first choice for patients with oral ulcerations both in our study and in the literature ( 7 ), only behind traditional remedies in certain countries, which have been proved to increase the risk for presenting with advanced disease stage at diagnosis ( 19 ). Studies on cancer patients confirm the preference for physicians ( 20 ), with the only exception of Japan, where dentists are reported to be the clinician of choice ( 21 ).…”
Section: Discussionmentioning
confidence: 91%